(untitled) (Encuentros, 2024)
This article presents certain interpretive trends of Latin American interculturality, its applications, and the key debates it confronts on its path to establishing itself as a political and educational proposal for social transformation. Three perspectives are discussed: interculturality as a leading political concept in the struggles of indigenous movements, interculturality and dialogue of knowledge as ethical-political proposals for acknowledging epistemological pluralism, and finally, interculturality in the educational realm as a fundamental tool for social change. It is concluded that, despite the controversies, interculturality is a theoretical field that allows for continued reflection on the phenomena inherent to spaces of cultural interaction, and enables the development of conceptual frameworks and analytical tools to address the challenges that arise in multicultural contexts.